Atlas of West African urban food systems: examples from Ghana and Burkina Faso - Karg, H.; Drechsel, Pay (International Water Management Institute, 2018)
This Atlas summarizes recent advances in interdisciplinary approaches and research to address the different components of West African urban food systems, including urban and peri-urban agriculture. It thereby draws on the results of several major collaborative research projects and stakeholder consultations conducted in West Africa over the past two decades, and in particular on the UrbanFoodPlus project in Ghana and Burkina Faso (www.urbanfoodplus.org). The publication targets with its innovative design a broad range of stakeholders.